2023
DOI: 10.1186/s12891-023-06334-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-magnitude, variable-frequency vibration therapy on pain threshold levels and mobility in adults with moderate knee osteoarthritis—randomized controlled trial

Abstract: Background Osteoarthritis (OA) is one of the most commonly recorded diseases in clinical practice. Vibration therapy has been suggested for the treatment of knee OA. The purpose of the study was to determine the impact of vibrations of variable frequency and low amplitude on pain perception and mobility in patients suffering from knee OA. Methods Thirty-two participants were allocated into two groups – Group 1 (oscillatory cycloidal vibrotherapy-OC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…The same results by Pasterczyk-Szczurek et al (27) showed that adult patients in the vibration group experienced less pain during anesthesia compared to the control group. They assessed pain levels using the VAS and the McGill Pain Questionnaire.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The same results by Pasterczyk-Szczurek et al (27) showed that adult patients in the vibration group experienced less pain during anesthesia compared to the control group. They assessed pain levels using the VAS and the McGill Pain Questionnaire.…”
Section: Resultssupporting
confidence: 67%
“…They assessed pain levels using the VAS and the McGill Pain Questionnaire. Additionally, they utilized extraoral vibrations, which may mitigate the effect of vibrations applied through the pain control gate mechanism due to the distance between the injection site and the device (27). Furthermore, Sharma et al (28) demonstrated a significant reduction in injection pain and discomfort after using their dental vibe injection system in adult volunteers.…”
Section: Resultsmentioning
confidence: 99%